High-performance torque controller design for AC driving 4WD electric vehicle in two time scales. (2018) - Fu, Zhi-Jun; Li, Bin; Ning, Xiao-Bin
In this paper, a novel torque control method of AC induction motor in two time scales is proposed for 4WD electric vehicles. A two-time-scale sliding-mode control (SMC) observer and a SMC controller are synthesised to ensure high-performance torque control. Two time scales are considered based on the natural time scale separation existed in the AC induction motor driving system, i.e., rotor flux and speed corresponding to the slow dynamics and the stator current corresponding to the fast dynamics. The convergence property of the controller is considered when performing the observer design rather than the conventional control method where the controller and observer are designed separately. Moreover, the more advanced space vector modulation (SVM) technology instead of the sinusoidal pulse width modulation (SPWM) method used in the conventional SMC is also introduced in the proposed method to achieve minimum torque ripple. The effectiveness of the proposed torque control method is illustrated through simulations on a 4WD electric vehicle. Simulation results illustrate the improved performance compared with the conventional SMC method.